2007
DOI: 10.1002/art.22294
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk with intermittent high‐dose oral glucocorticoid therapy

Abstract: Objective. To evaluate the risk of fracture in patients receiving intermittent therapy with high-dose oral glucocorticoids (GCs).Methods. The study group comprised 191,752 patients from the UK General Practice Database who were 40 years of age and older and received therapy with GCs. The followup time period was divided into the categories of "current" and "no exposure." The daily dose and cumulative dose for each time period were determined. Relative risks were estimated using Cox proportional hazards models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(196 citation statements)
references
References 20 publications
8
171
1
11
Order By: Relevance
“…in the present study, both the higher initial dose and the greater numbers of gc dose-increase were two independent risk factors. The increased fracture risk with intermittent high-dose oral gc therapy was recently demonstrated by others [33], indicating that the exposure to high gc dose during a long period of time might produce the bone damage. however, the very high gc dose with a short period of exposure may not be what induces the damage, since gc pulse therapy was not correlated to bone fracture.…”
Section: Discussionmentioning
confidence: 77%
“…in the present study, both the higher initial dose and the greater numbers of gc dose-increase were two independent risk factors. The increased fracture risk with intermittent high-dose oral gc therapy was recently demonstrated by others [33], indicating that the exposure to high gc dose during a long period of time might produce the bone damage. however, the very high gc dose with a short period of exposure may not be what induces the damage, since gc pulse therapy was not correlated to bone fracture.…”
Section: Discussionmentioning
confidence: 77%
“…In fact, recent studies showed that the relative risk (RR) of clinical vertebral fracture in patients receiving oral glucocorticoid therapy was 2.6 and, thus, much greater than that for hip fractures (RR 1.6) or nonvertebral fractures (RR 1.3) (31,32). Moreover, fractures in glucocorticoid-induced osteoporosis occur at thresholds of BMD (T score of Ϫ1.5) that are above those of postmenopausal osteoporosis (31,32). Consistent with the clinical data, prednisolone treatment of hRANKL-knockin mice predominantly caused loss of bone mass and bone strength at the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a familiar adverse effect of a few classes of drugs, including glucocorticoids 71,72 and aromatase inhibitors, 73 and a strongly suspected adverse effect with others, such as proton pump inhibitors (PPIs) or SSRIs. Although the drugs may have been prescribed for the best of clinical reasons, there may be a potential for risk modification by successfully controlling diseases with drugs that are not harmful to the skeleton (for example, using H2 blockers instead of PPIs where possible) or by modifying risk by co-administration of osteoporosis drugs.…”
Section: Drug Exposuresmentioning
confidence: 99%